2016
DOI: 10.1111/gcbb.12390
|View full text |Cite
|
Sign up to set email alerts
|

Does soil aging affect the N2O mitigation potential of biochar? A combined microcosm and field study

Abstract: The application of biochar as a soil amendment to improve soil fertility has been suggested as a tool to reduce soil-borne CO 2 and non-CO 2 greenhouse gas emissions, especially nitrous oxide (N 2 O). Both laboratory and field trials have demonstrated N 2 O emission reduction by biochar amendment, but the long-term effect (>1 year) has been questioned. Here, we present results of a combined microcosm and field study using a powdered beech wood biochar from slow pyrolysis. The field experiment showed that both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 65 publications
3
23
0
Order By: Relevance
“…Furthermore, the calculation of cumulative NO 3 − -derived N 2 O emissions showed that soil biochar amendment significantly decreased N 2 O emissions by 54%. These results confirmed what has been shown in several lab and field studies before11646566676869, that biochar amendment can mitigate soil N 2 O emission. In addition to N 2 O emission reduction, Cayuela and colleagues showed that soil biochar amendment substantially decreased the N 2 O/(N 2 O + N 2 ) emission ratio64.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the calculation of cumulative NO 3 − -derived N 2 O emissions showed that soil biochar amendment significantly decreased N 2 O emissions by 54%. These results confirmed what has been shown in several lab and field studies before11646566676869, that biochar amendment can mitigate soil N 2 O emission. In addition to N 2 O emission reduction, Cayuela and colleagues showed that soil biochar amendment substantially decreased the N 2 O/(N 2 O + N 2 ) emission ratio64.…”
Section: Discussionsupporting
confidence: 90%
“…Adding rice straw-derived biochar in a paddy soil reduced CH 4 emission under ambient and elevated temperature and CO 2 , attributed to the decreased microbial activity along with the increased CH 4 oxidation activity [188]. Soilborne emissions are predominantly the major sources of N 2 O in the air [32] caused mainly by nitrogen transformation microbes in the soil through nitrification and denitrification. Suppression of N 2 O becomes an important climate change mitigation, varying with biomass source and pyrolysis environment.…”
Section: Ghgs Emissionmentioning
confidence: 99%
“…Increasing number of studies were conducted in recent years to explore the microbial mechanisms of biocharinduced changes in N 2 O/CH 4 emissions from soil (Hagemann et al 2017;Han et al 2016a;Harter et al 2016;Sun et al 2018;Wang et al 2017c). The development of distinct N 2 O-reducing microbial taxa induced by biochar might lower N 2 O emission (Harter et al 2016).…”
Section: Biochar and Global Climate Changementioning
confidence: 99%